Studies in Judaism: Second series - Schechter, S. (The Jewish Publication Society of America, 1908)
A hoard of Hebrew manuscripts I.--A hoard of Hebrew manuscripts II.--The study of the Bible.--A glimpse of the social life of the Jews in the age of Jesus the sons of Sirach.--On the study of the Talmud.--The memoirs of a Jewess of the seventeenth century [Frau Glückel von Hameln]--Saints and saintliness.--Four epistles to the Jews of England.--Safed in the sixteenth century, a city of legists and mystics.